Fab : the coming revolution on your desktop - from personal computers to personal fabrication. - Gershenfeld, Neil A., 1959- (New York : Basic, 2005)
What if you could someday put the manufacturing power of an automobile plant on your desktop? According to Neil Gershenfeld, the renowned MIT scientist and inventor, the next big thing is personal fabrication-the ability to design and produce your own products, in your own home, with a machine that combines consumer electronics and industrial tools. Personal fabricators are about to revolutionize the world just as personal computers did a generation ago, and Fab shows us how.